The Many Faces of Populism : Perspectives from Critical Theory and Beyond - Byrd, Dustin J.; Ivanovic, Mlado; Morelock, Jeremiah (Social Sciences E-Books Online, Collection 2025., 2025)
Today, more than ever, it is easy to understand how populism has become such a contested word in contemporary politics. Despite its relatively short history, the term follows a rather volatile trajectory in terms of its historical development and presence as a political practice. When we look at its political and moral impact, one can see that despite its often strict national commitments and narratives, populism is rather a global political phenomenon. As embodiment of anti-establishment narratives, polarizing attitudes, and emancipatory appeal, we can follow its occurrence from Central and Eastern Europe, Latin America, the USA and UK, the Middle East, all the way to China and India. This edited volume helps fill a gap in the existing literature on Critical Theory (broadly construed) and populism, focusing on the multiple dimensions of historical and contemporary contexts for today's rising populist movements and their often - but not necessarily - hostile relations towards cosmopolitanism, globalization, environmentalism, and general notions of inclusion and justice. Contributors are: Emília Barna, Ronald Beiner, Dustin J. Byrd, Samir Gandesha, Carlos Antonio Giovinazzo Júnior, Mlado Ivanovic, Yonathan Listik, Grigoris Markou, Jeremiah Morelock, Felipe Ziotti Narita, Ágnes Patakfalvi- Czirják, Maria Cristina Dancham Simões and Hassan Zaheer. See Less